1998
DOI: 10.1108/09576069810210448
|View full text |Cite
|
Sign up to set email alerts
|

On‐machine measurement of workpieces with the cutting tool

Abstract: A new system for on‐machine measurement of workpieces is described. The system is based on a fine touch sensor that enables the cutting tool itself to act as a contact probe to inspect the workpiece. The proposed measurement technology combines the Q‐setter with the fine touch sensor. This low cost measurement system is applied to automatic workpiece setup and improving workpiece dimensional accuracy on a CNC turning center. It is shown that using the proposed measurement system results in workpiece setting ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The measurement technology can be divided into on-machine measurement, in situ measurement, and off-machine measurement; according to the measuring time and location, it can be divided into pre-process measurement, in-process measurement, and post-process measurement [21][22][23][24][25][26].…”
Section: Workpiece Measurement Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement technology can be divided into on-machine measurement, in situ measurement, and off-machine measurement; according to the measuring time and location, it can be divided into pre-process measurement, in-process measurement, and post-process measurement [21][22][23][24][25][26].…”
Section: Workpiece Measurement Technologymentioning
confidence: 99%
“…The error at the end of the workpiece reaches a maximum of ~0.035 mm and needs to be compensated several times before its size is within the set tolerance range. As the purpose of rough machining is to remove excess materials quickly and cut with large feed and cutting depth, the size error is larger when the workpiece is further away from the clamping end [24,29]. After finish machining, it can be found that the errors can be kept within the set Since the positioning accuracy of the machine and spindle, probe calibration, and the surface quality after machining will be reflected in the accuracy of contact probe measurement in actual machining [22,25,[27][28][29], it will lead to the results shown in Table 3 and Figure 8.…”
Section: Effects Of Turning and Milling On On-machine Measuringmentioning
confidence: 99%
See 1 more Smart Citation
“…A forgácsolási folyamatoknál is alkalmazhatunk olyan mérést, mely megszakítja a folyamatot, ilyen például a munkadarab beméréssel végzett szerszámkorrekció, amely egy adott megmunkálóciklus végén kerül elvégzésre. Ezen felül megkülönböztetünk folyamat előtt vagy után végzett méréseket, mely nem a megmunkáló program része, ilyen például a beépített szerszámbemérővel történő szerszámbemérés felszerszámozásnál [2].…”
Section: Bevezetésunclassified